Short Report: Saturation Rate after Vaccination against COVID-19 - Mohr, Arno; Hitzenbichler, Florian; Pfeifer, Michael; Hinterberger, Thilo; Loew, Thomas H; Leinberger, Beate (Archives of Clinical and Biomedical Research, 2022)
Introduction: Cormirnaty® was the first available vaccine in Europe that contains mRNA encoding the spike protein of SARS-CoV2. An enormous peptide commonality and thus molecular mimicry between SARS-CoV2 spike protein and human proteins could be shown. Molecular mimicry could be attributable to SARS-CoV2 associated illness. Objectives: So far saturation rate was not examined in patients who received Cormirnaty®. A decline in saturation rate would be suggestive that main reason for respiratory failure in patients with COVID-19 is the immune response to the spike protein. Method: The study was conducted at the Centre of Pneumology in Donaustauf, Germany. Employees that qualified for vaccination against COVID-19 and who were willing to be vaccinated with Cormirnaty® (second dose) were asked to participate in this study. Participants were asked to measure saturation rate three times a day for seven days after vaccination. Results: 106 participants (84 female, 22 male) were included into the analysis. Mean oxygenation satur-ation measured directly after vaccination was 97.4% (max 99%, min 93%. During days two to five, mean oxygen saturation dropped to 97.2% (max 99%, min 83%). This difference was significant in a one-tailed signed rank test with z=-1.88 (p=0.030). Conclusion: A mild but significant decline in satu-ration could be detected. As Cormirnaty® comprises mRNA for encoding peptides of the spike protein the decline in saturation rate might hint that molecular mimicry is an important element of COVID-19.